2000
DOI: 10.1084/jem.192.10.1425
|View full text |Cite
|
Sign up to set email alerts
|

Lymph-Borne Chemokines and Other Low Molecular Weight Molecules Reach High Endothelial Venules via Specialized Conduits While a Functional Barrier Limits Access to the Lymphocyte Microenvironments in Lymph Node Cortex

Abstract: Lymph-borne, soluble factors (e.g., chemokines and others) influence lymphocyte recirculation and endothelial phenotype at high endothelial venules (HEVs) in lymph node cortex. Yet the route lymph-borne soluble molecules travel from the subcapsular sinus to the HEVs is unclear. Therefore, we injected subcutaneously into mice and rats a wide variety of fluorophore-labeled, soluble molecules and examined their distribution in the draining lymph nodes. Rather than percolating throughout the draining lymph node, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
517
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 523 publications
(546 citation statements)
references
References 57 publications
21
517
1
Order By: Relevance
“…In contrast, APC and soluble antigens arrive via afferent lymphatic vessels and enter the lymph node via the subcapsular sinus. Functional studies using fluorescently labeled tracers have previously demonstrated that soluble antigens do not freely diffuse into the lymph node parenchyma containing the lymphocytes, but are rather contained within the subcapsular sinus [3]. Most of the lymph is channeled around the lymphocyte compartment towards the medullary sinuses, a labyrinth of lymphatic vessels and sinuses at the hilus of the lymph node.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, APC and soluble antigens arrive via afferent lymphatic vessels and enter the lymph node via the subcapsular sinus. Functional studies using fluorescently labeled tracers have previously demonstrated that soluble antigens do not freely diffuse into the lymph node parenchyma containing the lymphocytes, but are rather contained within the subcapsular sinus [3]. Most of the lymph is channeled around the lymphocyte compartment towards the medullary sinuses, a labyrinth of lymphatic vessels and sinuses at the hilus of the lymph node.…”
Section: Introductionmentioning
confidence: 99%
“…Two distinct distribution patterns of soluble lymph-borne molecules in the lymph node have been reported. Large molecules are retained in subcapsular and medullary sinuses, whereas small lymph-borne molecules with a molecular weight below 70 kDa or a diameter smaller than 4 nm can gain access to the cortex of lymph nodes [3]. Their transport is directed by a network of collagen type I -containing reticular fibers ensheathed by a single layer of fibroblastic reticular cells (FRC) [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear how this could be concluded since Kelly had not carried out a tridimensional analysis of the presumed cords, a necessary task given their reportedly complex geometry and the acknowledged difficulty of distinguishing them in normal lymph nodes (Kelly, 1975;Gretz et al, 1997). Moreover, it is disconcerting that the ''paracortical cords'' were not mentioned 1 year earlier in a proposal on how ''paracortex'' morphology facilitates the triggering of a cellular response (Gretz et al, 1996) or a few years later in an article examining APC-lymphocyte interaction (Gretz et al, 2000). In our opinion, the existence of these cords is unsubstantiated.…”
Section: Reticular Fiber Network and Pathways Of Transcortical Cell Mmentioning
confidence: 99%
“…Injecting instead a foreign albumin, Sainte-Marie and Peng (1986) observed its transport by fibers running through the thickness of the subcapsular sinus, subsinus layer, extrafollicular zone, deep cortex periphery, and adjoining HEV basement membranes; no endothelial permeation was detected. Recently, Gretz et al (2000) stated that drained fluorophore-labeled low MW dextrans and proteins diffused from peri-HEV fibers in between HEV cells and into an HEV's lumen. However, in the absence of counterstaining with a standard technique, it is questionable whether the small pale structures in their supporting Fig.…”
Section: Functional Aspects Of the Lymph Node Compartment Transport Omentioning
confidence: 99%